BREAKING THE VICIOUS CYCLE OF POVERTY - Yuana Tri Utomo (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
This simple article expresses ideas on how to break the vicious cycle of poverty caused by the implementation of the economic system of Capitalism whose distribution of wealth is unfair and unequal. Information is taken by qualitative methods through library research from various references, such as articles in reputable journals, books in libraries, and other documents that have been legally published. The results of the analysis of some of the information found that the way to break the vicious cycle of poverty is to leave the economic system of capitalism and replace it with an Islamic economic system.